The Effect of Adding Plastic Bottle Waste Fiber on the Compressive and Split Tensile Strength of Concrete - K Muhawalah , M. A Fahmi, J Prasetiawan (Jurnal Handasah, 2025)
Plastic bottle waste is a fairly serious problem, considering the large number of mineral water products produced by several companies and the behavior of people who litter. The addition of plastic bottle waste that is used as fiber is one of the efforts to reduce environmental pollution and reduce the amount of existing plastic bottle waste The method in this study refers to SNI 03-2834-2000 using PET type plastic bottle waste fiber with mixed percentage variations of 0.00%, 0.6%, 1.3% and 2% as an additive to the concrete mixture by using the test object. cylinder. The concrete is planned to be fc '20 MPa, the tests carried out are in the form of testing the compressive strength and split tensile strength using a Compression Testing Machine (CTM). From the results of the study at 28 days, it was found that the compressive strength value with mixed variations decreased from the normal concrete by 31.52 Mpa, 29.91 Mpa, 28.31 Mpa and 26.89 Mpa, the value of split tensile strength in all variations of the mixture also decreased. of normal concrete are 3.84 Mpa, 3.58 Mpa, 3.37 Mpa, and 2.99 Mpa. Optimal compressive strength is found in 0.6% mixture of 29.91 Mpa. The optimal tensile strength is found in the 0.6% mixture variation, with a tensile value of 3.58 Mpa.